2016
DOI: 10.1680/jener.16.00011
|View full text |Cite
|
Sign up to set email alerts
|

Briefing: Conventional, wind and solar energy resources in Oman

Abstract: Energy has become an important sector in the strategy termed: Omani vision 2020. Renewable energy sources can form a vital and strategic solution for the provision of electric power in the Sultanate. This paper provides a comprehensive review of Oman conventional and renewable energy resources (wind and solar). Although Oman in not currently utilizing its renewable energy resources, this study reveals that renewable energy resources such as wind and solar are have enough potential which can be directly utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Gulf Cooperation Council (GCC) member countries (Saudi Arabia, Oman, United Arab Emirates, Kuwait, and Qatar) are considered as major consumers of the natural resources, which results in a huge amount of emissions [9,10]. Similarly, the annual solid waste generation in the GCC region has exceeded 150 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…Gulf Cooperation Council (GCC) member countries (Saudi Arabia, Oman, United Arab Emirates, Kuwait, and Qatar) are considered as major consumers of the natural resources, which results in a huge amount of emissions [9,10]. Similarly, the annual solid waste generation in the GCC region has exceeded 150 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…Another agenda of the Oman Vision 20-40 plan in diversifying the economy is for Oman to invest in renewable energy [3]. Furthermore, due to the demand for a greener environment in the 21st century, there has been a growing demand for renewable energy sources both globally and within Oman [3][4][5][6][7][8]. The availability of renewable energy can not only provide a continuous power supply, but also supply an energy demand balance in the electrical power system [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Oman, the electricity consumption is comparatively low than other GCC countries as Oman is somehow beyond in terms of infrastructures development and industrialization. Umar and Wamuziri (2016) explore the potential of wind and solar energy in Oman and found that there is a huge opportunity to use these resources. Since ancient times biomass has played an important role in the society, and is nowadays used as fuel in a wide range of applications, such as cooking, heating and power generation.…”
Section: Introductionmentioning
confidence: 99%